Determinants of Umrah Pilgrims’ Satisfaction: The Mediating Role of Trust - Yanti, Juli Darma; Fitri, Anisa Tul; Mustika, Ruri; Novia, Aidil; Wira, Ahmad (LP2M IAIN Palopo, 2025)
This study aims to examine the effect of service quality, price perception, experiential marketing on Umrah pilgrims' satisfaction with trust as a mediating variable. The research method used is quantitative with data analysis techniques using SEM (Structual Equation Model) with Smart-PLS. The results of this study reveal that only one direct effect is positive and significant, namely: Service quality has a positive but insignificant effect on Umrah pilgrims' satisfaction, perceived price has a negative and insignificant effect on Umrah pilgrims' satisfaction, Experiential marketing has a positive but insignificant effect on Umrah pilgrims' satisfaction, trust has a positive and significant effect on Umrah pilgrims' satisfaction, service quality has a positive but insignificant effect on Umrah pilgrims' trust, price perception has a positive but insignificant effect on the trust of Umrah pilgrims, experiential marketing has a negative and insignificant effect on trust, service quality through trust has a positive and insignificant effect on the satisfaction of Umrah pilgrims, price perception through trust has a positive and insignificant effect on the satisfaction of Umrah pilgrims, and experiential marketing through trust have a positive and insignificant effect on Umrah pilgrims' satisfaction. Keywords: Service Quality; Price Perception; Experiential Marketing; Satisfaction dan Trust. Keywords: Service Quality; Price Perception; Experiential Marketing; Satisfaction dan Trust.